Check-in behaviour and spatio-temporal vibrancy: An exploratory analysis in Shenzhen, China. (July 2018) - Wu, Chao; Ye, Xinyue; Ren, Fu; Du, Qingyun
Abstract: Urban vibrancy describes the attraction, diversity and accessibility of a place and exhibits spatio-temporal variability. The relationships between urban vibrancy and land-use configurations are significant for governments, planners and residents. To date, it is challenging for traditional census datasets to support real-time analysis with detailed spatial and temporal granularity. This article takes advantage of emerging crowdsourcing data and adopts social media check-ins over a 24-h period as a proxy for urban vibrancy. A framework that incorporates kernel density estimation (KDE), geographically and temporally weighted regression (GTWR) and the Herfindahl-Hirschman index (HHI) is proposed to explore the spatio-temporal distribution characteristics of vibrancy and the spatio-temporal relationships with the influential factors. The results show that the evolution of vibrancy is influenced by various factors that are heterogeneous over space and time. With a new perspective and deeper understanding of the varying spatio-temporal relationships between vibrancy and point of interest (POI)-based configurations, this study can offers meaningful implications for policy makers and planners regarding the improvement of resource utilization and the rational design of neighbourhoods. Highlights: Social media Check-ins is applied as a proxy of urban vibrancy. Spatial-temporal effects of POI-based configurations on vibrancy are analysed. Policy suggestions are offered to improve resource utilization and design neighborhood rationally.